2021
DOI: 10.1002/ctm2.479
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA IL6‐AS1 is highly expressed in chronic obstructive pulmonary disease and is associated with interleukin 6 by targeting miR‐149‐5p and early B‐cell factor 1

Abstract: 1. The study provides the evidence that a novel lncRNA IL6-AS1 is highly expressed in COPD and is associated with inflammation. 2. IL6-AS1 acts as the competitive endogenous RNA (ceRNA) to competitively bind to hsa-miR-149-5p to regulate IL-6 expression. 3. IL6-AS1 acts as a guide to promote the gene expression via recruiting EBF1 to the region of the IL-6 promoter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 74 publications
1
38
0
Order By: Relevance
“…EGFR-mediated signaling is likely to be the predominant driver of airway remodeling and mucus cell hyperplasia in CS-induced COPD pathogenesis, and this pathway may not involve SPDEF-mediated mucous responses ( 11 , 37 ). In terms of molecular regulation of other inflammatory factors' expression, lncRNAs are shown to act as molecular sponges/scaffolds for miRNAs as reported recently in COPD ( 38 40 ). For example, lncRNA TUG1 promotes airway remodeling via suppressing the miR-145-5p in CS-induced COPD models.…”
Section: Discussionmentioning
confidence: 66%
“…EGFR-mediated signaling is likely to be the predominant driver of airway remodeling and mucus cell hyperplasia in CS-induced COPD pathogenesis, and this pathway may not involve SPDEF-mediated mucous responses ( 11 , 37 ). In terms of molecular regulation of other inflammatory factors' expression, lncRNAs are shown to act as molecular sponges/scaffolds for miRNAs as reported recently in COPD ( 38 40 ). For example, lncRNA TUG1 promotes airway remodeling via suppressing the miR-145-5p in CS-induced COPD models.…”
Section: Discussionmentioning
confidence: 66%
“…Existing research indicated that epigenetic mechanisms are associated with the disease progression in COPD ( 166 ). A novel lncRNA, interleukin 6 antisense RNA 1 (IL6-AS1) supposed to recruit early B-cell factor 1 to the IL-6 promoter to increase the H3K4 methylation and H3K27 acetylation, therein, increases airway inflammation in COPD ( 27 ). SUV39H1 is a histone methyltransferase; the levels of SUV39H1 and H3K9me3 were reduced in COPD patients.…”
Section: Histone Modifications In Inflammatory Diseasesmentioning
confidence: 99%
“…Previous research has shown that the dysregulation of miR-149-5p is closely associated with malignant tumor progression, metastasis, and chemoresistance in gastric cancer (31)(32)(33), papillary thyroid cancer (34), colorectal cancer (35)(36)(37), and breast cancer (38). Additionally, miR-149-5p is also involved in the pathogenesis of inflammationassociated diseases, such as the PM 2.5 -induced inflammatory response (39), rheumatoid arthritis (40), and chronic obstructive pulmonary disease (41). In recent years, it has been reported that miR-149-5p plays crucial roles in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%